PENINGKATAN PEMASARAN PADA UMKM LAHANG AREN GULA SEMUT DANWEDANG JAHE MELALUI DIGITAL DI DESA WAY KALAM KECAMATAN PENENGAHAN KABUPA1TEN LAMPUNG SELATAN - Zuriana, Zuriana; AK Yohanson, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The community service work practice program is a means of self-actualization of several skills orskills, both soft skills or hard skills that have been obtained during lectures, which will be applied inthe community for 1 month.In this community service practice report, our participants will take partin the Program, which is located in Way Kalam Village and Gula Semut UMKM, South Lampung for 1 month, from January 31, 2022 to March 2, 2021.The placement of this community servicepractice is located at the Sugar Ants SMEs located in Way Kalam village.Here I will focus on the use of social media for digital marketing to improve marketing and also make ant sugar products forthe Haris Pratama Ants Sugar SMEs.As well as participating in village activities, including: road repair work, mutual cooperation, helping the Way Kalam village tourism awareness group,measuring and mapping village land assets and holding a farewell event at the village hall